The Effects of Margin of Appreciation Doctrine on the European Court of Human Rights: Upholding Public Morality over Fundamental Rights - Itır Aladağ Görentaş (Akademik İncelemeler Dergisi)
The European Court of Human Rights’ (the Court, ECtHR) granting opportunityto Contracting States to strike a balance between the public goodand the interests of the individuals is designated as “margin of appreciationdoctrine”. Unfortunately, the Court is facing harsh crtitism applying thedoctrine to especially cases concerning the violation of Article 9- freedomof thought, conscience and religion and Article 10- freedom of expression,since it seems to lack standards in application. In this study, the EuropeanCourt of Human Rights’ controversial application of margin of appreciationdoctrine to freedom of religion and freedom of expression will be addressed.The discussion will seek to analyse the reasons behind the Court’s significantdiscretion affording to Contracting States when Article 9 and Article 10cases are in question.